1997
DOI: 10.1108/02635579710367270
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of quality practices: USA, China and India

Abstract: Seeks to compare the quality management practices in three different countries: USA, India and China. For this research various constructs representing quality management practices and quality results were conceptualized. A questionnaire survey instrument was developed, pretested and the final version of the questionnaire incorporated the results of pretesting. The final questionnaire was used to collect data in the USA, India, and China. Analysis of variance was used to analyse the data. Reports the statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 18 publications
1
52
0
1
Order By: Relevance
“…They noted that transferring quality practices from a home country to another country or in another way are required to achieve overall business objective and to consider similarities and differences in the context globalization. Meanwhile, Raghunathan et al (1997) surveyed 228 USA, 78 China and 168 Indian manufacturing including automotive industries. They found that it is important to consider quality practices between developed and developing countries to understand the status and there may be opportunities for developing countries to learn from the successes and failures of the quality practices of developed countries.…”
Section: Quality In International Contextmentioning
confidence: 99%
“…They noted that transferring quality practices from a home country to another country or in another way are required to achieve overall business objective and to consider similarities and differences in the context globalization. Meanwhile, Raghunathan et al (1997) surveyed 228 USA, 78 China and 168 Indian manufacturing including automotive industries. They found that it is important to consider quality practices between developed and developing countries to understand the status and there may be opportunities for developing countries to learn from the successes and failures of the quality practices of developed countries.…”
Section: Quality In International Contextmentioning
confidence: 99%
“…In fact, most of their research was negatively affected by a lack of theoretical grounding, clear methodology, objective statistical evidence, reliability and validity testing, and of control for extraneous factors (Flynn et al, 1994;Powell, 1995;Raghunathan et al, 1997;Singhal, 1997, 2001;Sousa and Voss, 2002).…”
Section: Discussion and Implications For Research And Managementmentioning
confidence: 99%
“…Rungtusanatham et al, 2005;, while others concluded the opposite (e.g. Adam et al, 1994Adam et al, , 1997Raghunathan et al, 1997;Tata et al, 2000;Tarí et al, 2007).…”
Section: Several Explanations Can Be Advanced For the Apparent Improvmentioning
confidence: 99%
See 1 more Smart Citation
“…ANOVA analysis is frequently used by researchers (e.g., Cherrett, et al, 2009;He, et al, 2011;Raghunathan, et al, 1997) in deciding whether to claim the concerned viewpoints or attributes, etc. are different between different groups.…”
Section: Literature Sources Supporting and Inspiring The Proposition mentioning
confidence: 99%